2014
DOI: 10.1007/s40471-013-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Implications for Women’s Reproductive Health

Abstract: Obesity is an epidemic in the developed world. In the U.S., over one-third of women are now obese, with significant adverse consequences for their reproductive and longterm health. Many of these women gain excessive weight in pregnancy and retain it postpartum, with an additive effect across multiple pregnancies. Maternal obesity is associated with an increased risk for miscarriage, congenital anomalies, stillbirth, gestational diabetes, preeclampsia, and cesarean section. Offspring of obese women are at incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 104 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…In addition, this state of surge in inflammatory cytokines is also responsible for the release of certain proteins and interleukins which inhibit the insulin signaling pathways, interfering with the insulin release and leading to potentially elevated blood sugar levels and gestational diabetes. 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this state of surge in inflammatory cytokines is also responsible for the release of certain proteins and interleukins which inhibit the insulin signaling pathways, interfering with the insulin release and leading to potentially elevated blood sugar levels and gestational diabetes. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current meta-analysis was to evaluate the effects of gestational weight gain on maternal and fetal outcomes in women with twin pregnancies., Methods: A systematic search was conducted using the PubMed, Scopus, and Google Scholar databases. Studies, either retrospective or prospective in design, evaluating the effects of gestational weight gain (defined using Institute of Medicine (IOM included eleven papers and concluded that inadequate weight gain in mothers with twin pregnancy led to increased risk of gestational diabetes, reduced risk of hypertension and cesarean delivery among mothers and increased risk of PTLBW 38 , SGA and NICU admission in neonates. Moreover, excessive weight gain was associated with increased risk of preeclampsia and cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, chronic maternal health issues may lead to increased maternal investment in somatic effort, at the expense of both parental effort and future reproductive opportunities, thereby decreasing a man's prospects of future reproduction and possibly lowering his likelihood of remaining with the mother. Obesity is associated with lower odds of conception and higher odds of pregnancy loss (Brewer and Balen 2010; Chin et al 2014), in part through its association with polycystic ovary syndrome (PCOS), the most common endocrinological disorder among reproductive-aged women (Unger 2012). Type 2 diabetes is also associated with adverse birth outcomes, including pregnancy loss, congenital abnormalities, preterm delivery and low birthweight (Anderson et al 2016; Kinsley 2007; Roland et al 2005).…”
Section: Predicting Paternity Establishmentmentioning
confidence: 99%